(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Distance education is a mainstream instrument in India these days for individuals who need to procure information and overhaul capability. Education play a vital role in development of any country, so that it’s take more attention of People of any country. In the present study we analyze the challenges occurred in the distance education, the distance education effect in Indian education system, the Participation of women in distance education and distance mode quality of education.